PEMIKIRAN INTELEKTUAL MUSLIM TENTANG KRISTENISASI DI INDONESIA 1966-1998 - Mansur, Syafiin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
Christian is the second largest religion in Indonesia, after Islam. The relation between Christian and Islam frequently emerges prejudices, misunderstandings, and conflicts. Based on the historical records, Christians frequently refused the Government’s rules that have been agreed by the adherents of all religions in Indonesia due to the interests  of Christianization developed from Portuguese and Dutch colonial era until the Independence Day of Indonesia. The efforts of Christianization seems more aggressive after the dissolution of the communist party and during New Order era.  As a result, many communist people and the poors became the Christians at that time. The Christians’ efforts to convert the believers of other religions in Indonesia, especially Muslims, were done by various ways and forms, and they still continue to this day.This Paper answers several main research questions as follow: how is the portrait of Christianization In Indonesia from 1966-1998?; how are the responses of Mohammad Natsir, Hasbullah Bakry and Abujamin Roham as Muslim intellectuals in mapping Christianization in Indonesia?; and how are the efforts of these figures in stemming Christianization in Indonesia?. This paper hows that Christianization in Indonesia is still taking place up to the present.  Even though on the name of social activities, the efforts of Christianization in the New Order era were conducted systematically, well-organized, and carefully planned so that they succeeded to convert Muslims to be Christians satisfactorily. Such condition was admitted by Mohammad Natsir, Hasbullah Bakry, and Abujamin Roham so that they strictly responded and stated that Christianization has violated Pancasila and UUD 1945 as well as infringed the ethics of proselytizing that potentially evoked prejudices, conflicts, and destruction  of inter-religious harmony in Indonesia. Those three figures made serious efforts to weir Christianization in Indonesia by writing scientific works dealing with Christianization in Indonesia in order to fortify faith and strengthen the unity of Muslims, training and preparing professional proselytizers, performing dialogues and discussions, and fostering inter-religious harmony so as to create peace and unity of Indonesi.Keywords: Mohammad Natsir, Hasbullah Bakry, Abujamin Roham, Pemikiran, Intelektual, Kristenisasi, Toleransi, Kerukunan, Indoensia.